Computational Study of the Thermodynamic Properties of Some Lead-free Solder Alloys - Sah, Sanjay Kumar; Jha, Indu Shekhar; Koirala, Ishwar (BMC Journal of Scientific Research, 2022)
Activities of the components of the binary lead-free solder alloys Cu-Sn, and Ag-Cu were computed using the molecular interaction volume model (MIVM). The theoretical data have been compared with the corresponding experimental values. For the validity of the model parameters, the excess Gibbs free energy of mixing of Cu-Sn, and Ag-Cu liquid alloys have been determined and compared with the corresponding experimental data available in the literature. Similarly, the activities of Sn in ternary liquid alloys Sn-Ag-Cu were computed and examined with the available experimental data at 1000 K. It has been observed that the calculated activities of the components of the binary and ternary solder alloys have nearly the same tendency as the experimental data.